2017
DOI: 10.18001/trs.3.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Exposure and Smoke-free Policy in Philadelphia Public Housing

Abstract: Objectives Multi-unit housing environments remain significant sources of secondhand smoke (SHS) exposure, especially for vulnerable populations in subsidized housing. In Philadelphia, the largest US housing authority to implement smoke-free policies, we measured baseline resident smoking-related behaviors and attitudes, and longitudinal exposures to airborne nicotine, during policy development and implementation. Methods In 4 communities, we collected data in 2013, 2014, and 2016, before and after introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The findings of this study are consistent with those of other studies examining the association of SFH policies with SHS exposure. 15,16,18 One recent study 18 studies, these authors found that Boston SFH policy implementation was associated with greater decreases in PM 2.5 and airborne nicotine concentration 1 year after the policy implementation compared with housing that had no policy, although the association was not equal at all sites. 16 To our knowledge, evidence of persistently reduced SHS over time has not been published.…”
Section: Discussionmentioning
confidence: 98%
“…The findings of this study are consistent with those of other studies examining the association of SFH policies with SHS exposure. 15,16,18 One recent study 18 studies, these authors found that Boston SFH policy implementation was associated with greater decreases in PM 2.5 and airborne nicotine concentration 1 year after the policy implementation compared with housing that had no policy, although the association was not equal at all sites. 16 To our knowledge, evidence of persistently reduced SHS over time has not been published.…”
Section: Discussionmentioning
confidence: 98%
“…Only a few studies have measured changes in SHS exposure before and after implementation of housing-wide bans [21, 22]. While several studies have examined the post-implementation impacts of SFH on self-reported SHS exposure [21, 2325], as of early 2019 only researchers in Boston and Philadelphia have evaluated a smoking ban in public housing apartments using state-of-the-art objective measures of SHS exposure such as airborne nicotine and particulate matter less than 2.5 μm in aerodynamic diameter (PM2.5) concentrations [22, 2629]. An early cross-sectional study in Boston ( n = 32 non-smoker apartments) found significantly lower PM2.5 concentrations and airborne nicotine levels in buildings with smoke-free policies compared with buildings without a similar ban [28].…”
Section: Introductionmentioning
confidence: 99%
“…An early cross-sectional study in Boston ( n = 32 non-smoker apartments) found significantly lower PM2.5 concentrations and airborne nicotine levels in buildings with smoke-free policies compared with buildings without a similar ban [28]. However, results from these studies were inconsistent with respect to whether such policies result in detectable reductions in airborne nicotine or particulate matter (PM) in the homes of non-smoking residents, in part due to the challenges of small sample sizes and limited durations of post-policy follow up [22, 27, 29]. To foster harmonization of methods across studies examining similar policies, we present our detailed protocol here.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of children are exposed to SHS at home, and the most common source of inhome SHS are household members, such as smoking parents 5,6 . However, children can also be exposed at home from external sources: smoking visitors 6 , incursion of SHS from the outside environment 7,8 , and attendant "thirdhand" smoke from these elements 9 .…”
Section: Introductionmentioning
confidence: 99%